Altered Protein Kinase C Regulation of Pulmonary Endothelial Store- and Receptor-Operated Ca(2+) Entry after Chronic Hypoxia - Paffett, Michael L. (The American Society for Pharmacology and Experimental Therapeutics, 2010)
Chronic hypoxia (CH)-induced pulmonary hypertension is associated with decreased basal pulmonary artery endothelial cell (EC) Ca(2+), which correlates with reduced store-operated Ca(2+) (SOC) entry. Protein kinase C (PKC) attenuates SOC entry in ECs. Therefore, we hypothesized that PKC has a greater inhibitory effect on EC SOC and receptor-operated Ca(2+) entry after CH. To test this hypothesis, we assessed SOC in the presence or absence of the nonselective PKC inhibitor GF109203X [2-[1-(3-dimethylaminopropyl)-1H-indol-3-yl]-3-(1H-indol-3-yl)maleimide] in freshly isolated, Fura-2-loaded ECs obtained from intrapulmonary arteries of control and CH rats (4 weeks at 0.5 atm). We found that SOC entry and 1-oleoyl-2-acetyl-sn-glycerol (OAG)- and ATP-induced Ca(2+) influx were attenuated in ECs from CH rats versus controls, and GF109203X restored SOC and OAG responses to the level of controls. In contrast, nonselective PKC inhibition with GF109203X or the selective PKC(ε) inhibitor myristoylated V1-2 attenuated ATP-induced Ca(2+) entry in ECs from control but not CH pulmonary arteries. ATP-induced Ca(2+) entry was also attenuated by the T-type voltage-gated Ca(2+) channel (VGCC) inhibitor mibefradil in control cells. Consistent with the presence of endothelial T-type VGCC, we observed depolarization-induced Ca(2+) influx in control cells that was inhibited by mibefradil. This response was largely absent in ECs from CH arteries. We conclude that CH enhances PKC-dependent inhibition of SOC- and OAG-induced Ca(2+) entry. Furthermore, these data suggest that CH may reduce the ATP-dependent Ca(2+) entry that is mediated, in part, by PKCε and mibefradil-sensitive Ca(2+) channels in control cells.